The risk of risk management: adopting critical theories to explore clinical risk concerns in mental health care. Issue 2 (11th October 2021) - Deering, Kris; Williams, Jo; Williams, Rob
Abstract : Purpose: The purpose of this paper is to outline several critical risk theories and explore their application to risk concerns in mental health care. This will contribute to the on-going debate about risk management practices and the impact these might have on recovery and social inclusion. Notably, while risks like suicide can be therapeutically addressed, risk management may involve paternalistic practices that exclude the participation needed for recovery. Design/methodology/approach: A viewpoint of key risk theories will be presented to provide a critical eye about some clinical risk concerns in mental health care. Implications for recovery and social inclusion will then be discussed alongside direction for practice and research. Findings: Clinical concerns seemed to involve difficulties with uncertainty, holding onto expertise, and the othering of patients through risk. These concerns suggest the patient voice might become lost, particularly within the backdrop of clinical fears about blame. Alternatively, a relational approach to risk management could have merit, while patient expertise may develop understanding in how to improve risk management practices. Originality/value: Clinical concerns appear more than managing potential harms; it can involve appraising behaviours around societal norms, explaining to an extent why mental illness might be addressed in terms of risks. While the points raised in the paper support existing findings about risk management, the underlying reasons drawing on the critical risk theories are less explored.